Survey of Basic Motor Skills of Fifth Grade Students at Gugus Nusa Indah, Mranggen District, Demak Regency - Nikcyta Kumala Puspa; Agung Wahyudi (Indonesian Journal for Physical Education and Sport, 2025)
This study aims to analyze the basic motor skills of fifth-grade students in five elementary schools in the Nusa Indah Cluster, Mranggen District, Demak Regency. This study uses a quantitative descriptive method with data collection techniques in the form of basic motor skills tests covering various indicators, such as sprinting, shuttle runs, ball throwing and catching, and stand positional strokes. The results of the analysis show that the majority of students are in the “Moderate” category (41.94%), while a small number of students are in the “Very Good” (5.65%) and “Very Poor” (6.45%) categories. The variation in results between schools is due to several factors, such as the quality of school facilities, field conditions, and student motivation levels. Schools with better facilities, such as SD N Mranggen 2 and SD N Mranggen 4, showed higher student performance. However, SD N Mranggen 1 and SD N Mranggen 3 faced challenges in the form of a lack of student enthusiasm and inadequate fields. Based on these results, the study recommends improving sports facilities, student motivation programs, and the involvement of female students in physical activities. With the right interventions, it is hoped that the basic motor skills of students in these schools will improve and develop optimally.